2014
DOI: 10.1039/c4ay00633j
|View full text |Cite
|
Sign up to set email alerts
|

Laser ionization/time-of-flight mass spectrometry for the direct analysis of emulsions

Abstract: A direct method for the monitoring of emulsions was developed using laser ionization/time-of-flight mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…17 With this technique, we demonstrated the possibility of evaluating the creaming of emulsions from the time course of a peak area. 15 In the present study, we demonstrated the possibility of a quantitative analysis of an oil component in an emulsion via MPI-TOFM, which has not been achieved. We constructed a calibration curve of styrene, as an oil phase, in an O/W emulsion.…”
Section: 27mentioning
confidence: 99%
See 2 more Smart Citations
“…17 With this technique, we demonstrated the possibility of evaluating the creaming of emulsions from the time course of a peak area. 15 In the present study, we demonstrated the possibility of a quantitative analysis of an oil component in an emulsion via MPI-TOFM, which has not been achieved. We constructed a calibration curve of styrene, as an oil phase, in an O/W emulsion.…”
Section: 27mentioning
confidence: 99%
“…This system consists of a pair of concentric capillary columns. 15 By using MPI-TOFMS combined with this introduction system, we continuously obtained a series of mass spectra, and then constructed a time profile of the peak area of a constituent. Previously, we often found intense spikes on the time profiles for a constituent of an oil phase in an oil-in-water (O/W) emulsion; such spikes indicated the existence of oil droplets or their aggregates.…”
Section: 27mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also applied LI-TOFMS to the measurement of liquid samples, 34,35 including emulsions. [36][37][38][39] In the present study, we treated TiO2 nanoparticles with PTES and prepared slurry samples where PTES either remained or was removed by washing. Then, a direct mass analysis of the slurries was performed by LI-TOFMS, and we confirmed whether the remaining PTES could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recently, we reported on the use of vaporization and subsequent ionization techniques for measuring of a liquid sample without using a frit. 14,15 Volatile compounds in aqueous solution are usually detected online. 14 In that report, we irradiated a pulsed laser for vaporization to an inlet nozzle, and analyte molecules could be partially introduced in a pulsed form.…”
Section: Introductionmentioning
confidence: 99%